Deflection Reliability Analysis for Composite Steel Bridges - Mohammed, D.; Al-Zaidee, S. R. (Engineering, Technology & Applied Science Research, 2022)
Reliability methods offer a very efficient serviceability assessment of structures with randomness due to geometry, material, and loading. Al-Awsej composite bridge in Diyala-Iraq with a span of 33.2m has been studied and its deflection reliability index for three lifespans was estimated and compared with the reliability target index. The reliability indices of the bridge have been evaluated through the First-Order Reliability Method (FORM) and Monte Carlo Simulation (MCS) method. MCS has adopted Matlab functions to generate pseudo-random numbers for the considered parameters, but it requires large sample sizes to estimate the small probabilities of failure. That leads to the use of the reduction variance methods such as the Importance Sampling (IS) method. Four cases of random loading were included: dead load and three cases of live loads, i.e. uniformly distributed load with knife-edge load, military load, and sidewalk load. Some assumptions are needed to assess the system behavior, where the bridge is represented as a parallel system with uncorrelated and perfect correlated girders. The reliability index of the composite bridge in the two cases was investigated for lifespans of 1, 10, and 50 years. For the uncorrelated case, the system shows the reliability index in the range of 5 and 4. In contrast, the correlated case offers a range between 4 and 2. With these assumptions, the results show that no failure occurs, hence the reliability index of the system is still within range of the target.